2000
DOI: 10.1212/wnl.55.10.1455
|View full text |Cite
|
Sign up to set email alerts
|

Childhood mental ability and dementia

Abstract: Late-onset dementia is associated with lower mental ability scores in childhood. Early-onset dementia mental ability scores did not differ from locally matched control subjects or from late-onset dementia. Mechanisms that account for the link between lower mental ability and late-onset dementia are probably not relevant to early-onset dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
181
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 34 publications
9
181
2
2
Order By: Relevance
“…No such association has been detected for early onset dementia, but lower IQ at age 11 has been associated with increased risk of late-onset dementia. 15 However, this study comprised only 50 late-onset cases, so was inadequately powered to determine effects of childhood IQ on AD and VaD separately. The Nun Study also found an association between linguistic ability at about 22 years of age and late-onset dementia, but this was based on just 39 neuropathology cases, only 59% of whom fulfilled clinical diagnostic criteria for dementia.…”
Section: Discussionmentioning
confidence: 99%
“…No such association has been detected for early onset dementia, but lower IQ at age 11 has been associated with increased risk of late-onset dementia. 15 However, this study comprised only 50 late-onset cases, so was inadequately powered to determine effects of childhood IQ on AD and VaD separately. The Nun Study also found an association between linguistic ability at about 22 years of age and late-onset dementia, but this was based on just 39 neuropathology cases, only 59% of whom fulfilled clinical diagnostic criteria for dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Braak and Braak (1999) showed that AD-related pathology can be seen as early as in the third decade of life. However, AD pathology is unlikely to be a major factor in 11-year-olds (Whalley et al, 2000).Another possibility is that these findings reflect the consequences of early life environment, which has been linked to the later development of such chronic adult diseases as heart disease and diabetes (Osmond & Barker, 2000). Nutrient limitation in utero and infancy leads to changes of structure and metabolism that are the origin of hypertension and diabetes in adulthood.…”
mentioning
confidence: 93%
“…The participants have been followed up for mortality and cancer since inception, and have recently been linked with the Scottish Morbidity Records (SMR) system, enabling data on physical and mental illness to be investigated. 16 , related to lifetime psychiatric contact 17 , and a risk factor for mortality 18 and for senile but not pre-senile dementia in later life 19 .…”
Section: Introductionmentioning
confidence: 99%